HAMKA SEBAGAI KETUA UMUM MUI (MAJELIS ULAMA INDONESIA) DALAM MENGHADAPI MASALAH SOSIAL POLITIK PADA MASA ORDE BARU 1975-1981 - Wildan Insan Fauzi (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
Feeling the need for an alternative channel of communication with the Muslim community, in 1975 the government established a national Council of Ulama, the ‘Majelis Ulama Indonesia’ (MUI). MUI was establish to some purpose like mobilising Muslim support for the government’s development policies, although officially meant to facilitate two-way communication, in practice the council’s function is, as aptly formulated by the present Minister of Religion, “to translate government policy into a language that the ummah understands, Its functions are reminiscent of the traditional office of the shaykh al-islam, issuing fatwa to legitimise government policies; its ability to modify these policies is only very marginal.